The retirement migration puzzle in China - Chen, Simiao; Jin, Zhangfeng; Prettner, Klaus (GLO discussion paper, 2020)
We examine whether and how retirement affects migration decisions in China. Using a regression discontinuity (RD) design approach combined with a nationally representative sample of 228,855 adults aged between 40 and 75, we find that retirement increases the probability of migration by 12.9 percentage points. Approximately 38% of the total migration effects can be attributed to inter-temporal substitution (delayed migration). Retirement-induced migrants are lower-educated and have restricted access to social security. Household-level migration decisions can reconcile different migration responses across gender. Retirees migrate for risk sharing and family protection mechnisms, reducing market production of their families in the receiving households.
Keywords: Graue Literatur